Effect of Cyproheptadine on Ventilatory Support-free Days in Critically Ill Patients with COVID-19: An Open-label, Randomized Clinical Trial - Boniatti, Márcio Manozzo (2023)
Background: Serotonin is a mediator of pulmonary hypoxic vasoconstriction. Experimental studies have shown that serotonin-mediated pulmonary vasoconstriction can be inhibited by cyproheptadine. The aim of this study is to assess whether treatment with cyproheptadine compared to usual care increases ventilatory support-free days during the first 28 days in patients with coronavirus disease 2019 (COVID-19) requiring ventilatory support. Materials and methods: This randomized, single-center, open-label clinical trial included patients who were admitted to the intensive care unit (ICU) requiring ventilatory support due to COVID-19. Patients allocated to the intervention group received cyproheptadine for 10 days. The primary outcome was ventilator-free days during the first 28 days. Results: Nineteen patients were randomized to receive cyproheptadine and 21 to the control group. The number of ventilatory support-free days during the first 28 days was not different between the two groups (15.0; 95% CI, 0.0–24.0 days in the control group vs 7.0; 95% CI, 0.0–19.0 days in the intervention group; p = 0.284). Conclusion: In patients with COVID-19 and in need of ventilatory support, the use of cyproheptadine plus usual care, compared with usual care alone, did not increase the number of ventilatory support-free days in 28 days.